2002
DOI: 10.1021/ma010587h
|View full text |Cite
|
Sign up to set email alerts
|

Surface Order in Thin Films of Self-Assembled Columnar Liquid Crystals

Abstract: The way in which alignment of hexagonal columnar mesophases depends on molecular structure, film thickness, and surface interactions is investigated. Homeotropic orientation of tapered nonpolymeric and polymeric amphiphilic columnar molecules occurs most readily on carbon substrates. The planar alignment of asymmetric dendrimers is favored on a water surface but is not possible for a symmetric dendrimer. For the polymeric material, film thickness has a significant influence on the morphology. Thick films align… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 32 publications
4
49
0
Order By: Relevance
“…[38] X-ray and STM results have been compared for some LC compounds and similarities as well as differences for the lattice parameters and unit cells obtained from these two methods have been reported. [37a-c] The area of the 2D lattices of the columnar structures obtained from powder XRD and the cyclic structures observed by STM for ZnChl 1 are compared in order to verify whether similar molecular arrangement prevails within the column stratum of the LC phases as on the surface.…”
Section: Wwwchemeurjorg Discussionmentioning
confidence: 99%
“…[38] X-ray and STM results have been compared for some LC compounds and similarities as well as differences for the lattice parameters and unit cells obtained from these two methods have been reported. [37a-c] The area of the 2D lattices of the columnar structures obtained from powder XRD and the cyclic structures observed by STM for ZnChl 1 are compared in order to verify whether similar molecular arrangement prevails within the column stratum of the LC phases as on the surface.…”
Section: Wwwchemeurjorg Discussionmentioning
confidence: 99%
“…[7] In addition to the traditional columnar phases constructed with discogenic molecules with flexible tails, novel discotic LC systems have also been made from different building blocks such as chiral molecules, [8] inverted molecules, [9] or even dendrimers. [10] One of the new ideas in columnar discotic LCs is the development of self-assembly through noncovalent interactions. In these systems, columnar LC phases are not formed via discotic molecules or main-chain macromolecules, but rather by supramolecular discs as building blocks generated from rod-shaped [11] or half disc-shaped [12] molecules through intra/intermolecular noncovalent interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is quite usual to have homeotropic alignment of LCs squeezed between two substrates, a general strategy for achieving such an alignment in open films is still lacking, and studies of LC alignment in this geometry are very scarce to date. [6][7][8] Generally, the orientation of columns in open films is believed to result from competition between the homeotropic and homogeneous, or inplane, alignment (top panel of Fig. 1) due to the difference in the surface tensions between air/LC and LC/substrate.…”
mentioning
confidence: 99%
“…1) due to the difference in the surface tensions between air/LC and LC/substrate. [7] It was found that such an alignment is governed by the substrate surface energy, [8] chemical structure of the molecules, [9][10][11][12] and/or the sample thermal history such as cooling rate [13] or annealing temperature and time. Recently, it was observed that homeotropic alignment in films confined between two surfaces could be facilitated by irradiating the sample with circularly polarized infrared light at the wavelength corresponding to vibration of a chosen chemical bond of the LC molecule.…”
mentioning
confidence: 99%